2013
DOI: 10.1111/tbj.12151
|View full text |Cite
|
Sign up to set email alerts
|

Pre-mastectomy Sentinel Lymph Node Biopsy: A Strategy to Enhance Outcomes in Immediate Breast Reconstruction

Abstract: The pre-mastectomy sentinel lymph node biopsy (PM-SLNB) is a technique that provides knowledge regarding nodal status prior to mastectomy. Because radiation exposure is associated with poor outcomes in breast reconstruction and reconstructed breasts can interfere with the planning and delivery of radiation therapy (RT), information regarding nodal status has important implications for patients who desire immediate breast reconstruction. This study explores the safety and utility of PM-SLNB as part of the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…A problem with this strategy is that as many as 32% of breasts expanders exposed to radiation fail during the reconstruction process and require explantation 28 . An alternative approach that allows for a better determination of the need for PMRT prior to mastectomy and immediate reconstruction is the pre-mastectomy sentinel lymph node biopsy (PM-SLNB) 33 . This is the technique employed at our institution wherein the sentinel lymph node biopsy is performed days to weeks in advance of the mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A problem with this strategy is that as many as 32% of breasts expanders exposed to radiation fail during the reconstruction process and require explantation 28 . An alternative approach that allows for a better determination of the need for PMRT prior to mastectomy and immediate reconstruction is the pre-mastectomy sentinel lymph node biopsy (PM-SLNB) 33 . This is the technique employed at our institution wherein the sentinel lymph node biopsy is performed days to weeks in advance of the mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it complicates surgical planning, impacting the required time in the operating theatre and the necessary intraoperative resources. Several studies suggested a staged SLNB procedure prior to mastectomy when IBR is planned [34][35][36] . While enabling a complete pathological evaluation of the SLN status before breast surgery, this strategy comes with the drawback of a two-step surgical procedure, including increased risk for infections, delay in definitive surgery, and increased arm morbidity and hospital costs 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…At some centers, a sentinel lymph node biopsy is performed 2–3 weeks prior to mastectomy to eliminate the uncertainty surrounding PMRT. 33 Whether this would change management in patients who indeed require PMRT is an interesting question for future research.…”
Section: Discussionmentioning
confidence: 99%